2018
DOI: 10.3126/jnhrc.v16i1.19371
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Postoperative Complications after Percutaneous Nephrolithotomy

Abstract: Background:To identify the perioperative factors associated with complications after percutaneous nephrolithotomy by classification of complications according to the modified Clavien scoring system and evaluation of the minor and major complications related to the procedure. Methods:A prospective study of all the percutaneous nephrolithotomy performed by standard technique within 1.5 years at Bir Hospital was made. Possible demographic, preoperative and intraoperative variables were included in the study and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Percutaneous nephrolithotomy is a minimally invasive and reproducible method for the treatment of kidney stones, and the procedure is repeatable. Although percutaneous nephrolithotomy has become the standard treatment for kidney stones, there is still a potential risk of complication [6–8].…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous nephrolithotomy is a minimally invasive and reproducible method for the treatment of kidney stones, and the procedure is repeatable. Although percutaneous nephrolithotomy has become the standard treatment for kidney stones, there is still a potential risk of complication [6–8].…”
Section: Discussionmentioning
confidence: 99%
“…As indicated by Mazzon et al and EL-Nahas et al, stone burden is not associated with achieving trifecta [8,9]. However, evidence is accumulating that stone burden is relevant to both the SFR and postoperative complications, which are 2 components of trifecta [23][24][25][26]. On the other hand, hydronephrosis degree is considered to be associated with a reduced SFR [11,27].…”
Section: Discussionmentioning
confidence: 99%
“…Forty-two (27.75%) had residual fragments of more than 4 mm size, whereas in current study low dose CT KUB done after 48 hours showed fragments >4mm in 10% of cases only. 3 …”
Section: Discussionmentioning
confidence: 99%
“… 1 Percutaneous nephrolithotomy (PCNL) is considered a surgical modality with highest stone free rate with relatively higher complication rate. 2 , 3 Post-operative imaging after stone surgeries has not been uniform. The heterogeneity of assessment is due to: modality of imaging used; X-ray alone, ultrasonography alone, X-ray and ultrasonography (USG) combined or Computed tomography (CT), timing of imaging and definition of stone free status: <2mm, <4mm or no fragments.…”
Section: Introductionmentioning
confidence: 99%